Local and Global Pollution and International Environmental Agreements in a Network Approach - Michael Günther; Tim Hellmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Increasing concerns about climate change have given rise to the formation of International Environmental Agreements (IEAs) as a possible solution to limit global pollution eff ects. In this paper, we study the stability of IEAs in a repeated game framework where we restrict to strategies which are simple and invariant to renegotiation. Our main contribution to the literature on IEAs is that we allow for heterogeneous patterns of pollution such that additional to a global eff ect of pollution there are local pollution e ffects represented by a network structure. We show that stable IEAs exist if the network structure is balanced. Too large asymmetries in the degree of local spillovers may however lead to non-existence of stable structures.
Keywords: C72; D85; Q50; 330